The potential of antibody-drug conjugates in immunotherapy for non-small cell lung cancer: current progress and future - Lin, Hongyu; Ma, Xinyu; Zhu, Xinhai; Zhong, Linru (Frontiers in Oncology, 2025)
Antibody-drug conjugates (ADCs) have gained significant attention as a promising therapeutic strategy for non-small cell lung cancer (NSCLC), combining the precision of monoclonal antibodies with the potent cytotoxic effects of chemotherapy. This review summarizes recent advancements in the development of ADCs for NSCLC, focusing on their mechanism of action, key components, and progress in clinical applications. By specifically targeting tumor-associated antigens, ADCs deliver cytotoxic agents directly to cancer cells, thereby enhancing therapeutic efficacy while minimizing systemic toxicity. Several ADCs, such as trastuzumab deruxtecan and sacituzumab govitecan, have shown encouraging results in clinical trials, particularly in tumors with molecular alterations like HER2 and TROP2. Additionally, the combination of ADCs with immune checkpoint inhibitors (ICIs) offers a novel and promising therapeutic avenue, potentially enhancing immune responses and overcoming tumor resistance. Despite these promising outcomes, challenges such as drug resistance, immune evasion, and toxicity persist. The novelty and focus of this article are to discuss the significance of optimizing ADCs design, exploring combination therapies, and enhancing safety management in improving treatment outcomes, with the aim of promoting the research and application of ADCs in the immunotherapy of NSCLC